Retrospective review of Infections in Children with β- Thalassemia - M Kadhim, Mezher; I Alezzi, Jalil; M Khaleel, Suad; A Hussein, Eman; Sh Mahmoud, Najdat (Diyala Journal of Medicine, 2020)
Background: The immune system aberrations perceived in thalassemic children are both qualitative and quantitative, concerning many components of immune system; infections are a common complication and they can be fatal. Objective: To study the thalassemic children for bacterial infection. Patients and Methods: This is a retrospective cohort study, it was carried out in Al-Batool Teaching Hospital from June - Dec 2017. Criteria for susceptibility of immune-compromised children for bacterial infection were used for thalassemia major and intermedia children with review of patients records and patients/ parents dialogue. Statistical analysis was done by statistical analysis of social sciences (SPSS 22), P-value was set at (0.05) level. A total number of 188 thalassemia children were involved in this study. Results: Five (2.7%) children were documented as having a clinically important bacterial infection giving an incidence of 0.23 infections per 100 children/ years, four infections were developed in non- splenectomized children giving a rate of (3%). Two bacterial sepsis and two children suffered from draining otitis media, whereas after splenectomy, only one child developed bacterial pneumonia (1.9%). Conclusion: Only few bacterial infections were developed in studied thalassemic children during the last 12 years. None of them fulfill the immunocompromised criteria.